The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.1164/rccm.200110-022oc
|View full text |Cite
|
Sign up to set email alerts
|

Apnea–Hypopnea Threshold for CO2 in Patients with Congestive Heart Failure

Abstract: To understand the pathogenesis of central sleep apnea (CSA) in patients with congestive heart failure (CHF), we measured the end-tidal carbon dioxide pressure (PET(CO2)) during spontaneous breathing, the apnea-hypopnea threshold for CO2, and then calculated the difference between these two measurements in 19 stable patients with CHF with (12 patients) or without (7 patients) CSA during non-rapid eye movement sleep. Pressure support ventilation was used to reduce the PET(CO2) and thereby determine the threshold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
114
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(121 citation statements)
references
References 28 publications
6
114
0
1
Order By: Relevance
“…354 Diuresis with a reduction in cardiac filling pressure also has been shown to reduce the severity of CSA, 340 but in some patients, the resulting metabolic alkalosis may promote CSA by narrowing the difference between ambient PaCO 2 and the PaCO 2 threshold for apnea. 355,356 ␤-Adrenergic blockade, which counters excess sympathetic activation and may modulate ventilatory responses in heart failure, 18 has been reported to decrease AHI in patients with CSA. 357 However, the increasing use of such antagonists in heart failure appears not to have altered the prevalence of CSA in this condition.…”
Section: Treatment Options In Csamentioning
confidence: 99%
“…354 Diuresis with a reduction in cardiac filling pressure also has been shown to reduce the severity of CSA, 340 but in some patients, the resulting metabolic alkalosis may promote CSA by narrowing the difference between ambient PaCO 2 and the PaCO 2 threshold for apnea. 355,356 ␤-Adrenergic blockade, which counters excess sympathetic activation and may modulate ventilatory responses in heart failure, 18 has been reported to decrease AHI in patients with CSA. 357 However, the increasing use of such antagonists in heart failure appears not to have altered the prevalence of CSA in this condition.…”
Section: Treatment Options In Csamentioning
confidence: 99%
“…On the other hand hypocapnia in HF subjects with impaired ejection fraction (mean EF 23%) was associated with increased number of AHI episodes and central apneas [30]. Thus, it may not be hypocapnia itself, but diminished difference between eupneic PCO 2 and apnea threshold, known as PCO 2 reserve that predisposes to CSA, as discussed earlier [24,25].…”
Section: Central Sleep Apneamentioning
confidence: 87%
“…Pathological mechanisms underlying CSA have been widely investigated within last decade and explained in detail in a recent monograph [24]. The important factors involved in pathophysiology of CSA are: diminished PCO 2 reserve (difference between eupneic PCO 2 and apnea threshold) [24, 25], and augmented central and peripheral hypoxic and hypercapnic chemosensitivity [26,27]. These will be discussed in details below (Fig.…”
Section: Central Sleep Apneamentioning
confidence: 99%
“…It was reported that CHF patients with CSA showed no rise in P ET CO 2 from wakefulness to sleep unlike patients without CSA whose P ET CO 2 increases during sleep (Xie et al 2002). This means the narrowed proximity of the eupneic PaCO 2 to the apnea threshold, which may be a crucial determinant of the susceptibility to apnea.…”
Section: P Et Comentioning
confidence: 98%